Peluang dan Tantangan Pendidikan Islam: (Analisis SWOT Pada Kebijakan Kurikulum Merdeka) - Hidayat, Rahmat; Usman, Jarjani; Suyanta, Sri (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2023)
Islamic education is a process of internalizing Islamic knowledge and values ​​to students through teaching, habituation, guidance, nurturing, supervision and potential development, in order to achieve harmony and perfection in life in this world and the hereafter. The Merdeka Curriculum emphasizes developing student potential with a more inclusive and creative approach. This is aimed at expanding the reach of education so that it can meet the needs of all students, including those with special needs. This curriculum also offers more flexibility in choosing learning materials that are more creative and innovative. And students as the center in curriculum development. This research uses a library research approach. For data related to literature, researchers will refer to policies and/or laws and regulations as well as books and articles related to the independent curriculum as primary sources and books and articles about Islamic education as secondary data, researchers will examine policies related to the independent curriculum using SWOT analysis to find opportunities and challenges for Islamic education in the Merdeka curriculum. Based on the discussion of the research that has been carried out, the results of this research show: Islamic education in the Merdeka curriculum is more about internalizing the values ​​of Islamic education. It is necessary to deepen the material and learning strategies related to Islamic education, so that it is more easily accepted by students. Government support is needed in socializing the implementation of the Merdeka curriculum, so that there is maximum understanding and implementation of the Merdeka curriculum, especially in the project to strengthen the profile of Pancasila students (P5) and the student profile of Rahmatan Lil Alamin (PPRA). Strong support and commitment is needed from various parties regarding the implementation of the Merdeka curriculum, especially the internalization of the values ​​of Islamic education.